2006
DOI: 10.1248/cpb.54.1040
|View full text |Cite
|
Sign up to set email alerts
|

New Constituents from Stems of Goniothalamus amuyon

Abstract: Two new compounds, goniothalesacetate (1) and goniothalesdiol A (2) together with goniodiol-7-monoacetate, goniodiol-8-monoacetate, leiocarpin C, liriodenine, griffithazanone A, 4-methyl-2,9,10-(2H)-1-azaanthracencetrione, velutinam and aristolactam BII were isolated and characterized from the stems of Goniothalamus amuyon. Structures of new compounds were determined by spectral analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…Hinweis: Wegen der endständigen Doppelbindung sollten die Bedingungen für die Abspaltung des Enders‐Auxiliars modifiziert werden, um eine Oxidation zum Keton zu vermeiden . b) Synthese von Goniothalesdiol A, identifiziert mit CSF=(RINGS+STEREO)⋅SMILES_LEN 2 +(RINGS+10⋅STEREO) und RSF=20+20⋅CONFLICT; c) Synthese von racemischem Juvabion, gefunden mit CSF=SMILES_LEN 2 und RSF=100+5⋅PROTECT+10⋅CONFLICT; d) Synthese eines aus Cryptocarya latifolia isolierten polyhydroxylierten Naturstoffs . Der Syntheseweg wurde mit CSF=10⋅RINGS+10⋅STEREO und RSF=5+20⋅PROTECT+50⋅CONFLICT ermittelt.…”
Section: Computergestützte Planung Von De‐novo‐synthesenunclassified
See 1 more Smart Citation
“…Hinweis: Wegen der endständigen Doppelbindung sollten die Bedingungen für die Abspaltung des Enders‐Auxiliars modifiziert werden, um eine Oxidation zum Keton zu vermeiden . b) Synthese von Goniothalesdiol A, identifiziert mit CSF=(RINGS+STEREO)⋅SMILES_LEN 2 +(RINGS+10⋅STEREO) und RSF=20+20⋅CONFLICT; c) Synthese von racemischem Juvabion, gefunden mit CSF=SMILES_LEN 2 und RSF=100+5⋅PROTECT+10⋅CONFLICT; d) Synthese eines aus Cryptocarya latifolia isolierten polyhydroxylierten Naturstoffs . Der Syntheseweg wurde mit CSF=10⋅RINGS+10⋅STEREO und RSF=5+20⋅PROTECT+50⋅CONFLICT ermittelt.…”
Section: Computergestützte Planung Von De‐novo‐synthesenunclassified
“…Ein weiteres Beispiel ist die Synthese von Goniothalesdiol A, das aus der Pflanze Goniothalamus amuyon isoliert wurde (Abbildung b) . Verbindungen aus dieser Klasse sind beliebte Syntheseziele, aber Synthesen von Goniothalesdiol wurden erst vor kurzem beschrieben .…”
Section: Computergestützte Planung Von De‐novo‐synthesenunclassified
“…Stem Anti-tumor, anti-platelet aggregation and anti-inflammation (Siripong et al 2006;Wu et al 1998;Punturee et al 2004) Annona squamosa Seed Cytotoxicity (Liaw et al 2008); anti-inflammation Goniothalamus amuyon Stem and root Cytotoxicity & anti-cancer (Lan et al 2003(Lan et al , 2006 Catharanthus roseus Stem Anti-cancer (van der Heijden et al 2004); antioxidant (Ferreres et al 2008) Emilia sonchifolia Stem Anti-inflammation and cytotoxicity (Muko and Ohiri 2000;Shylesh and Padikkala 2000) Artemisia argyi Stem Farnesyl protein transferase inhibitor (Lee et al 2002;Seo et al 2003) Ixeris chinensis Stem Antifebrile, antidotal, and analgesic effects (Zhang et al 2006) Euonymus spraguei Stem Not found…”
Section: Rhinacanthus Nasutusmentioning
confidence: 99%
“…The styryl lactones and acetogenins are two major types of bioactive compounds isolated from the Goniothalamus (Annonaceae) species. The structure and relative configuration of 1 were determined on the basis of NMR spectroscopy, and the absolute configuration was predicted by biosynthesis [2] (Fig. ).…”
mentioning
confidence: 99%